Long-term late toxicities and quality of life for survivors of nasopharyngeal carcinoma treated with intensity-modulated radiotherapy versus non-intensity-modulated radiotherapy - Huang, Tai-Lin; Chien, Chih-Yen; Tsai, Wen-Ling; Liao, Kuan-Cho; Chou, Shang-Yu; Lin, Hsin-Ching; Dean Luo, Sheng; Lee, Tsair-Fwu; Lee, Chien-Hung; Fang, Fu-Min (Head & neck, 2016)
Background The purpose of this study was to investigate late toxicities and quality of life (QOL) of patients with nasopharyngeal carcinoma (NPC) with long‐term survival after treatment by intensity‐modulated radiotherapy (IMRT) versus non‐IMRT. Methods An observational, cross‐sectional study of QOL and late toxicities was conducted in 242 patients with NPC with survival of >5 years after treatment with IMRT (n = 100) or non‐IMRT (n = 142) by using physician‐assessed toxicities (Common Terminology Criteria for Adverse Events [CTCAE] version 4) and the patient‐reported European Organization for Research and Treatment of Cancer Quality of Life Questionnaire‐Core 30‐questions (EORTC QLQ‐C30) and the Head and Neck 35‐questions (EORTC QLQ‐C30‐H&N35) module. Results The IMRT group had both statistically (p < .05) and clinically (difference of predicted mean scores ≥10 points) better outcome in global QOL, cognitive functioning, social functioning, fatigue, and 11 scales of the head and neck module. Late toxicities, including neuropathy, hearing loss, dysphagia, xerostomia, and neck fibrosis were significantly less severe in the IMRT group. Multivariate analysis revealed that the radiotherapy (RT) technique was statistically significantly associated with late toxicities and QOL outcome after adjusting for other clinical and demographic variables. Conclusion The use of the IMRT technique was associated with the improvement of physician‐assessed late toxicities and patient‐reported QOL in NPC survivors. © 2015 Wiley Periodicals, Inc. Head Neck 38: E1026–E1032, 2016